(3GdefjI hGdCed aj TQM cJGH Gdedd hGdfMds - (3CMeO Hf jMji Hf GdeQJVi Hf eaVd Hf efUhQ GdMSfj GdRjOi, J (B840 (3g`s
(3BNQgG (B:s
(3jfJgi HGdaUd GdKGdK ai GdcdGe Ydi GJHGY Cgd GdHjJ s
(3hgh GdSaQ GdChd ef GdZGjGJs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B140 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1821s
Keywords: (3GdJhMjO hGdedd hGdfMds